Case Report of Cutaneous Large B-cell leg-type Lymphoma in Young Woman - Bendari M.; Laajouri S.; Cherkaoui S.; Lamchahab M.; Quessar A.; Khoubila N. (European Scientific Journal, ESJ, 2019)
Cutaneous diffuse B-cell lymphoma leg type is a rare entity, it represents approximately 5% of primary cutaneous lymphomas. It has a poor prognosis. We report case of t 58 years old patient with a cutaneous B cell lymphoma leg type with dual location at the upper and lower limbs and bone lysis. Histological examination of the skin biopsy showed diffuse lymphomatous proliferation dissecting collagen, made of large cells with abundant cytoplasm moderately ill-defined, ovoid nuclei and with a discreet nuclear irregularity. The immunohistochemical study revealed lymphoma cells phenotype B with a homogeneous expression of CD 20, a homogeneous expression of CD 3, CD 43 positive. Bcl 2 was positive, asthe Bcl 6 and Mum 1. CD 5, CD10, MPO, CD 34, and Tdt were negative. The Ki 67 was positivein90%. The staging showed extensive osteolysis of the lower end of the humerus and the ulna. The patient received 2 courses RCHOP, with faillure of treatment, and then she received one course of RDHAP before dying. The particularity of this observation consists in the age; our patient was younger than the average, and the double localization of lymphoma in both arm and leg, with osteolysis. We discuss also the difficulties of treatment of this disease.